Fuss-free Filipino food quick & easy dishes for everyday cooking - Comsti, Angelo F.
With Spanish, Chinese and Malay influences, Filipino cuisine is distinct from that of its South East Asian neighbours with its sweet, salty, sour and spicy flavours. From staples such as port in shrimp paste, chicken in ginger soup, to snacks such as coconut and corn custard and sweet custard candy, Fuss-free Filipino food features some of the most popular dishes from across the archipelago, with quick and easy recipes that allow anyone to savour the comforting flavours of Filipino cooking without having to spend long hours in the kitchen.